FAKTOR – FAKTOR YANG MEMPENGARUHI PERATAAN LABA PADA PERUSAHAAN NON KEUANGAN - MONICA NOVIA GUNAWATI; YULIUS KURNIA SUSANTO (Jurnal Bisnis dan Akuntansi, 2019)
The purpose of this study is to examine the factors that influence income smooting in non-financial companies. These factors are size, leverage, profitability, ownership structure, institutional structure, firm value, and dividend payout ratio Population of this research are non financial companies listed in Indonesian Stock Exchange from 2014-2016. The samples are collected using purposive sampling method and there are 51 companies meet those criteria for samples. This research use logistic regression method for data analysis. The result of this research indicate that profitability has influence to income smoothing. While size, leverage,ownership structure, institutional structure, firm value and dividend payout ratio do not influence to income smoothing.